Development of a Hemispherical Cavity Cobalt Electrocatalyst for Water Oxidation Based on a Polystyrene Colloidal Template Electrodeposition Method. Issue 29 (1st August 2022) - Araki, Yusaku; Tsunekawa, Shun; Sakai, Arisu; Harada, Kazuki; Nagatsuka, Ryosuke; Suzuki‐Sakamaki, Masako; Amemiya, Kenta; Wang, Ke‐Hsuan; Kawai, Takeshi; Yoshida, Masaaki
Abstract: Hydrogen production through water electrolysis using renewable energy is expected to be one approach to solving current energy problems. The present report describes the development of a hemispherical cavity cobalt (Co) electrocatalyst with uniform pores with sizes of several hundred nanometers on the surface via electrodeposition on an indium tin oxide (ITO) substrate in a carbonate electrolyte solution using a polystyrene particle template. Catalytic activity measurements indicated that the cavity Co catalyst generated a greater oxygen evolution current compared to the flat Co catalyst. To investigate the electronic state and local structure, operando Co K‐edge XAFS measurements of the cavity Co catalyst were obtained under working conditions, which showed that Co species in the catalyst changed to one with a higher oxidation number while maintaining the local structure of CoOOH (CoO6 ). These results clarified that the cavity Co catalyst efficiently promoted water splitting through the uniform nanoscale pores with high oxidation Co in the CoOOH structure. Abstract : A cobalt carbonate electrocatalyst with a hemispherical cavity shape was developed for water splitting and oxygen evolution using a polystyrene colloidal template electrodeposition method in a potassium carbonate solution. Operando XAFS observations indicated that the cobalt species in this catalyst was Co with a high oxidation number in the CoOOH structure that functioned as a reaction site under working conditions.